2016
DOI: 10.21909/sp.2016.04.721
|View full text |Cite
|
Sign up to set email alerts
|

Do Men Conform More Than Women in the Recognition and Labeling of Emotions?

Abstract: Abstract:The study focuses on differences between women and men in recognizing negative emotions from facial expressions a nd the conformity of women and men while labeling the emotions. Previous research has indicated that women conform more than men when the stimuli used are more comprehensible for men. This research seeks to establish whether this phenomenon can be observed when the stimuli are more comprehensible to women. In this study, 24 women and 25 men labeled the facial expressions of negative emotio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…In terms of gender, earlier studies have reported an advantage of women in emotion recognition 19 , and that they pay more attention to the eyes than men, who pay more attention to the mouth than women do (morph of static pictures 20 , static pictures 15 ). Another study confirmed the dominance of women over men in labeling emotions, but a non-significant difference was found in tagging negative emotions 21 . Women’s superiority in emotion recognition seems to be maintained across aging 17 .…”
Section: Introductionmentioning
confidence: 91%
“…In terms of gender, earlier studies have reported an advantage of women in emotion recognition 19 , and that they pay more attention to the eyes than men, who pay more attention to the mouth than women do (morph of static pictures 20 , static pictures 15 ). Another study confirmed the dominance of women over men in labeling emotions, but a non-significant difference was found in tagging negative emotions 21 . Women’s superiority in emotion recognition seems to be maintained across aging 17 .…”
Section: Introductionmentioning
confidence: 91%